ASSESSMENT OF HUMAN BASIC MOVEMENT SYSTEMS BASED ON ARTIFICIAL INTELLIGENCE - Fayzullaev Bekhzod Bakhtiyorovich; Anarkulova Rano Oybek qizi; Jovliev Abbasjon Mirmukhsin (Galaxy International Interdisciplinary Research Journal, 2022)
One of the fastest growing areas today is artificial intelligence. This article gives a brief overview of the evaluation of human locomotor systems based on artificial intelligence. Today, information technology is developing rapidly in our lives.